Development of genomic simple sequence repeat markers for yam - Tamiru, M.; Yamanaka, S.; Mitsuoka, C.; Babil, P.; Takagi, H.; López Montes, Antonio José; Sartie, A.M.; Asiedu, Robert; Terauchi, R. (Wiley, 2015)
Yam ( Dioscorea spp.) is a major staple crop widely cultivated for its starchy tubers. To date, very few marker resources are publicly avail - able as tools for genetic and genomic studies of this economically important crop. In this study, 90 simple sequence repeat (SSR) markers were developed from an enriched genomic library of yellow Guinea yam ( D. cayenensis Lam.). Cross- amplification revealed that 85 (94.4%) and 51 (56.7%) of these SSRs could be successfully transferred to the two major cultivated species of D. rotundata Poir. and D. alata L., respec - tively. Polymorphisms in 30 markers selected on the basis of reliability and reproducibility of DNA bands were evaluated using a panel of 12 D. cayenensis , 48 D. rotundata , and 48 D. alata accessions. Accordingly, number of alleles per locus ranged from 2 to 8 in D. cayenensis (mean = 3.9), 3 to 30 in D. rotundata (mean = 13.9), and 2 to 22 in D. alata (mean = 12.1). The average observed and expected heterozygosi - ties were 0.156 and 0.634 ( D. cayenensis ), 0.326 and 0.853 ( D. rotundata ), and 0.247 and 0.836 ( D. alata ), respectively. Clustering based on six SSRs that were polymorphic in at least four of the five cultivated Dioscorea species studied, including D. cayenensis , D. rotundata , D. alata , D. dumetorum (Kunth) Pax., and D. bulbifera L., detected groups consistent with the phyloge - netic relationships of the species except for D. dumetorum . These new SSR markers are invalu - able resources for applications such as genetic diversity analysis and marker-assisted breedingYam ( Dioscorea spp.) is a major staple crop widely cultivated for its starchy tubers. To date, very few marker resources are publicly avail - able as tools for genetic and genomic studies of this economically important crop. In this study, 90 simple sequence repeat (SSR) markers were developed from an enriched genomic library of yellow Guinea yam ( D. cayenensis Lam.). Cross- amplification revealed that 85 (94.4%) and 51 (56.7%) of these SSRs could be successfully transferred to the two major cultivated species of D. rotundata Poir. and D. alata L., respec - tively. Polymorphisms in 30 markers selected on the basis of reliability and reproducibility of DNA bands were evaluated using a panel of 12 D. cayenensis , 48 D. rotundata , and 48 D. alata accessions. Accordingly, number of alleles per locus ranged from 2 to 8 in D. cayenensis (mean = 3.9), 3 to 30 in D. rotundata (mean = 13.9), and 2 to 22 in D. alata (mean = 12.1). The average observed and expected heterozygosi - ties were 0.156 and 0.634 ( D. cayenensis ), 0.326 and 0.853 ( D. rotundata ), and 0.247 and 0.836 ( D. alata ), respectively. Clustering based on six SSRs that were polymorphic in at least four of the five cultivated Dioscorea species studied, including D. cayenensis , D. rotundata , D. alata , D. dumetorum (Kunth) Pax., and D. bulbifera L., detected groups consistent with the phyloge - netic relationships of the species except for D. dumetorum . These new SSR markers are invalu - able resources for applications such as genetic diversity analysis and marker-assisted breeding